Unveiling the Environments of Extreme Massive Stars - Kraus, M. (2022)
Massive stars are powerful cosmic engines, enriching their environments withenergy and mass throughout their lifetime. The post-main sequence evolutionof massive stars comprises several distinct states, such as the luminous bluevariables, blue supergiants, red supergiants, Wolf-Rayet stars, B[e] supergiantsand yellow hypergiants, many of them connected with intense mass loss,embedding the stars in a dense environment. Here we present an overviewof our studies for members in three states of evolved massive stars: B[e]supergiants, luminous blue variables, and yellow hypergiants. Combininghigh-quality spectral and imaging observations over large wavelength regions,we aim to unveil the physical properties and temporal evolution of theejected material in these types of objects in order to gain insight into theirmass loss and mass ejection histories. This information is also vital to constrain the location of these objects along the evolutionary path of massive stars.